2014
DOI: 10.1039/c4ay01657b
|View full text |Cite
|
Sign up to set email alerts
|

Silica-based surface molecular imprinting for recognition and separation of lysozymes

Abstract: A highly selective surface molecularly imprinted inorganic polymer composed of tetraethoxysilane and 3-aminopropyltriethoxysilane has been prepared by a sol–gel process on silica submicroparticles in aqueous solution under simple and mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…protein is summarized briefly in Table 3. As can be seen, the resultant nanomaterials prepared in this work has a higher IF than those of other polymers [19, [35][36][37][38][39][40][41]. From this comparison, it can be found that MCNTs@Lyz-MIPs reported here constitute a significant improvement.…”
Section: Adsorption Isothermsmentioning
confidence: 45%
See 1 more Smart Citation
“…protein is summarized briefly in Table 3. As can be seen, the resultant nanomaterials prepared in this work has a higher IF than those of other polymers [19, [35][36][37][38][39][40][41]. From this comparison, it can be found that MCNTs@Lyz-MIPs reported here constitute a significant improvement.…”
Section: Adsorption Isothermsmentioning
confidence: 45%
“…Lyz-imprinted glass substrates ≈ 3.00 [38] Lyz-imprinted microspheres 2.36 [39] Lyz-imprinted thermo-responsive nanogel 2.47 [40] Lyz-imprinted silica submicroparticles 2.53 [41] MCNTs@Lyz-MIPs 4.00 This work…”
Section: [19]mentioning
confidence: 98%
“…10,11 Molecularly imprinted polymers (MIPs) are articial recognition materials with cavities that are formed by polymerization of functional monomers and cross-linkers around a target molecule aer template removal to specically bind that molecule. 12,13 They allow both sample pretreatment and enrichment and have been used in separation media, 14 and to mimic antibodies 15 as well as in chemical and biochemical sensing. 16 Molecularly imprinted solid-phase extraction (MISPE), which combines MIPs with SPE, has high selectivity, specicity and separation ability.…”
Section: Introductionmentioning
confidence: 99%
“…Surface imprinting using silica as the support has been applied to imprint pharmaceuticals [13][14][15][16][17][18] and biological macromolecules. 9,[19][20][21][22][23][24][25][26][27][28][29] Regrettably, the surface imprinting technology to prepare amino acid MIPs has been seldom reported.…”
Section: Introductionmentioning
confidence: 99%